Colloid coload versus crystalloid coload to prevent maternal hypotension in women receiving prophylactic phenylephrine infusion during caesarean delivery: a randomised controlled trial. (February 2022) - Park, S.-K.; Park, D.-N.; Kim, Y.-W.; Yoo, S.; Kim, W.H.; Lim, Y.-J.; Park, J.S.; Jun, J.K.; Kim, J.-T.
Highlights: Spinal anaesthesia was induced with a prophylactic phenylephrine infusion. Colloid was compared with crystalloid coload to prevent hypotension. The incidence of hypotension was not significantly different between groups. Abstract: Background: The optimal fluid strategy to prevent maternal hypotension during caesarean delivery remains unclear. This study aim was to compare the incidence of post-spinal anaesthesia hypotension in women receiving either colloid or crystalloid coload in the setting of prophylactic phenylephrine infusion during caesarean delivery. Methods: Healthy mothers undergoing elective caesarean delivery under spinal anaesthesia were randomised to receive a rapid intravenous coload with 6% hydroxyethyl starch 130/0.4 10 mL/kg (colloid group) or balanced crystalloid solution (Plasma Solution A) 10 mL/kg (crystalloid group) during spinal anaesthesia. All women had a prophylactic phenylephrine infusion initiated at 25 μg/min immediately after the subarachnoid block and titrated to systolic blood pressure using a standardised protocol. The primary outcome was the incidence of hypotension (systolic blood pressure <80% of baseline) until delivery. Results: The incidence of hypotension was 50% in the colloid group and 62% in the crystalloid group (absolute difference, −12% [95% CI −33% to 9%]; relative risk, 0.8 [95% CI 0.56 to 1.14]; P =0.314). No significant difference between groups was found in the number of hypotensive episodes (median 0.5 [IQR 0 to 1] vs 1 [0 to 2], P =0.132) or phenylephrine dose (675 [IQR 425 to 975] μg vs 750 [625 to 950] μg, P =0.109). The incidence of severe hypotension, symptomatic hypotension, bradycardia, nausea, and the neonatal outcomes were not significantly different. Conclusions: This study found no benefit of colloid coload compared with crystalloid coload for preventing maternal hypotension in the presence of prophylactic phenylephrine infusion during caesarean delivery.